Principles of Social Psychology (Open textbook library., 2015)
Have you ever had trouble teaching the various topics of social psychology and fitting them together to form a coherent field? Unnamed Author felt like he was presenting a laundry list of ideas, research studies, and phenomena, rather than an integrated set of principles and knowledge. He wondered how his students could be expected to remember and understand the many phenomena that social psychologists study? How could they tell what was most important? It was then that he realized a fresh approach to a Social Psychology textbook was needed to structure and integrate student learning; thus, Principles of Social Psychology was born. This textbook is based on a critical thinking approach, and its aim is to get students thinking actively and conceptually – with a greater focus on the forest than the trees. Yes, there are right and wrong answers, but the answers are not the only thing. What is perhaps even more important is how students get to the answers – the thinking process itself. To help students better grasp the big picture of social psychology, and to provide you with a theme that you can use to organize your lectures, Unnamed Author's text has a consistent pedagogy across the chapters. The presentation is organized around two underlying principles that are essential to social psychology: Person and Situation (the classic treatment)The ABCs of social psychology (Affect, Behavior, and Cognition) The author believes these dimensions are fundamental, that they are extremely heuristic, and that they are what he hopes your students (and his) will learn and remember. You may find that this organization represents a more explicit representation of what you're already doing in your lectures. Although the pedagogy is consistent, it is not constraining. You can and will use these dimensions more in some lectures than in others, and you will find them more useful for some topics than others. But they will always work for you when you are ready for them. Perhaps most important, a focus on these dimensions helps us bridge the gap between the textbook, the real-life experiences of our students, and our class presentations. It is almost impossible to can't cover every phenomenon in your lectures – you can naturally let the textbook fill in the details. The goal of Principles of Social Psychology is to allow you to rest assured that the text has provided your students with the foundations– the fundamental language of social psychology – from which you can build as you see fit. And when you turn to ask students to apply their learning to real life, you can know that they will be doing this as social psychologists do – using a basic underlying framework. A note about the organization of this text: it moves systematically from lower to higher levels of analysis – a method that makes sense to students. On the other hand, Unnamed Author insists, the chapter order should not constrain you – choose a different order if you wish. Chapter 1 presents an introduction to social psychology and the research methods in social psychology, Chapter 2 presents the fundamental principles of social cognition, and Chapter 3 focuses on social affect. The remainder of the text is organized around three levels of analysis, moving systematically from the individual level (Chapters 4-6), to the level of social interaction (Chapters 7-10) to the group and cultural level (Chapters 11-13). Rather than relying on “modules” or “appendices” of applied materials, this text integrates applied concepts into the text itself. This approach is consistent with the underlying theme that if students learn to think like social psychologists they will easily and naturally apply that knowledge to any and all applications. The following applications are woven throughout the text: Business and Consumer behavior Environment Health Law It is the "thinking like a social psychologist" theme, structured approach and new pedagogy (like research foci and Social Psychology in the Public Interest), that will make teaching and learning Social Psychology from this textbook an even more exciting and rewarding endeavor.